2020
DOI: 10.3390/metabo10100396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics Administration on Human Metabolic Phenotype

Abstract: The establishment of the beneficial interactions between the host and its microbiota is essential for the correct functioning of the organism, since microflora alterations can lead to many diseases. Probiotics improve balanced microbial communities, exerting substantial health-promoting effects. Here we monitored the molecular outcomes, obtained by gut microflora modulation through probiotic treatment, on human urine and serum metabolic profiles, with a metabolomic approach. Twenty-two subjects were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…Since few papers have assessed the effects of L. plantarum and L. reuteri strains and their synergy through a wide range of bacterial combination and supplementation levels, more studies are required to clarify the functional proprieties and the optimal inclusion level of these two bacterial strains on diarrhoea prevention in weaned piglets. In addition, probiotics may interact with the host metabolism [30] through their hypocholesterolemic and liver protection effects [31,32]. Furthermore, the bacterial combination does not always result in a synergistic effect, also showing possible competition among probiotic strains [33].…”
Section: Introductionmentioning
confidence: 99%
“…Since few papers have assessed the effects of L. plantarum and L. reuteri strains and their synergy through a wide range of bacterial combination and supplementation levels, more studies are required to clarify the functional proprieties and the optimal inclusion level of these two bacterial strains on diarrhoea prevention in weaned piglets. In addition, probiotics may interact with the host metabolism [30] through their hypocholesterolemic and liver protection effects [31,32]. Furthermore, the bacterial combination does not always result in a synergistic effect, also showing possible competition among probiotic strains [33].…”
Section: Introductionmentioning
confidence: 99%
“…In general, there seems to be a time-dependent association between metabolomic profiles and treatments. Probiotics can influence the levels of SCFA and other metabolites, but the effects might be specific to the individual (Ghini et al, 2020;Markowiak-Kopeć and Śliżewska, 2020). Previous studies have also reported that metabolomic profiles are more stable than microbiota profiles (Abdulkadir et al, 2016;O'Connell, 2020), which may indicate that the beneficial effects of probiotics may not be revealed solely by metabolomics analyses.…”
Section: Discussionmentioning
confidence: 99%
“…, food compounds) and some of them are exclusive of bacterial origin with a key role in host-microbiota cross-talk . These metabolic changes driven by bacteria have been documented at fecal, urine, and serum levels. , Dietary interventions are emerging as a strategy to reshaping and modulate not only the gut microbiota composition, but even their metabolomes, with concomitant positive effects on the hosts . Similarly, it is demonstrated that the administration of exogenous beneficial bacteria in a close pre-existent ecosystem generates metabolic mutualistic benefits for both the microbial community and the host. , …”
Section: Discussionmentioning
confidence: 99%
“…The probiotic blends were composed of strains of the Lactiplantibacillus plantarum, Lacticaseibacillus rhamnosus, Limosilactobacillus fermentum, and Bifidobacterium longum species and the period of the administration was characterized by a total of 8 weeks. As previously demonstrated, to have a more robust image of the metabolic behavior of the holobiont, a strong point that we proposed in this work is the use of different biofluids (urine and serum) and 20 samples per subject for urine, considered much more related to inherent variability than serum. Univariate and multivariate analyses were used to evaluate the one-dimensional (1D) NMR urine and serum spectra and to evaluate the effect of the probiotics on the human metabolome.…”
Section: Introductionmentioning
confidence: 99%